A method for calculating elliptic gear transmission efficiency based on transmission experiment - Dong, Changbin (Strojniški vestnik, 2021)
Transmission efficiency is an important index to evaluate the transmission performance and energy consumption of gear transmission systems. To analyse the transmission efficiency of elliptic gears, the load torque fluctuation model of elliptic gear is established to analyse the influence of load torque of an elliptic gear transmission system on the torque of input and output. The torque data of input and output under different working conditions are obtained by conducting an elliptic gear transmission test. Finally, the transmission efficiency of the elliptic gear pair is obtained through the torque measurement data of the elliptic gear transmission test, and its variation law under different working conditions is analysed. The results show that the transmission efficiency of the elliptic gear transmission system changes constantly and presents an increasing trend with the increase of load torque and a decreasing trend with the increase of speed.
Keywords: eliptični zobnik; elliptic gear; izkoristek prenosa; load fluctuation; navor; nihanje obremenitve; preskus prenosnika; torque; transmission efficiency; transmission test